2014
DOI: 10.3389/fimmu.2014.00261
|View full text |Cite
|
Sign up to set email alerts
|

Antigen-Pulsed CpG-ODN-Activated Dendritic Cells Induce Host-Protective Immune Response by Regulating the T Regulatory Cell Functioning in Leishmania donovani-Infected Mice: Critical Role of CXCL10

Abstract: Visceral leishmaniasis (VL), caused by Leishmania donovani, is a systemic infection of reticulo-endothelial system. There is currently no protective vaccine against VL and chemotherapy is increasingly limited due to appearance of drug resistance to first line drugs such as antimonials and amphotericin B. In the present study, by using a murine model of leishmaniasis we evaluated the function played by soluble leishmanial antigen (SLA)-pulsed CpG-ODN-stimulated dendritic cells (SLA–CpG–DCs) in restricting the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…The latter observation highlights the variable actions reported for CXCL10, since, depending upon the pathogen, model, and organ examined (53), CXCL10 deletion or neutralization can have no effect on (54, 55), reduce (51,52,56), or apparently even enhance (57, 58) host resistance to infection. CXCL10 also influences and recruits suppressive CXCR3 ϩ regulatory T cells to the tissues (59,60), and the absence of CXCR3 ϩ regulatory T cells might enhance the control of L. donovani replication in CXCL10 Ϫ/Ϫ mice. That said, however, it is not clear why early-stage infection was better controlled in CXCL10 Ϫ/Ϫ mice than CXCR3 Ϫ/Ϫ mice, although mice of both backgrounds showed similarly deficient initial mononuclear cell recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…The latter observation highlights the variable actions reported for CXCL10, since, depending upon the pathogen, model, and organ examined (53), CXCL10 deletion or neutralization can have no effect on (54, 55), reduce (51,52,56), or apparently even enhance (57, 58) host resistance to infection. CXCL10 also influences and recruits suppressive CXCR3 ϩ regulatory T cells to the tissues (59,60), and the absence of CXCR3 ϩ regulatory T cells might enhance the control of L. donovani replication in CXCL10 Ϫ/Ϫ mice. That said, however, it is not clear why early-stage infection was better controlled in CXCL10 Ϫ/Ϫ mice than CXCR3 Ϫ/Ϫ mice, although mice of both backgrounds showed similarly deficient initial mononuclear cell recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, even without molecular transfection approaches, CpG-ODN-stimulated DCs exhibited pivotal proinflammatory functions, as in a Leishmania donovani model intracellular parasitic growth was abolished by these CpG-stimulated DCs ( 41 ). Alongside, it was observed that DC vaccination resulted in significant decreased Treg numbers.…”
Section: Not Only Induce Treg But Also Limit Their Numbers By Convmentioning
confidence: 99%
“…CpG oligonucleotides (CpG ODNs) and CpG DNA can trigger intracellular signaling leading to the activation of macrophages, dendritic cells, and B cells, and the production of cytokines, chemokines, and immunoglobulins via TLR9 [ 7 ]. CpG ODNs have also been shown to stimulate the production of IL-10 by dendritic cells and promote the induction of T reg cells [ 17 ], and some parasite antigens can also initiate TLR9-dependent T reg cell activation [ 18 - 20 ]. T. spiralis has further been shown to induce T reg cell recruitment (with IL-10 and TGF-β as important cytokines) and regulate host Th2 and Th17 immune responses [ 4 ].…”
Section: Discussionmentioning
confidence: 99%